PENGARUH ELABORASI PESAN INFODEMIK VAKSIN COVID-19 TERHADAP PENGAMBILAN KEPUTUSAN VAKSINASI GENERASI Z (Survey Pada Masyarakat Dewasa Awal Wilayah Jakarta Timur) - Adam Abimanyu, (2023)
One way to overcome the Covid-19 outbreak is to carry out vaccinations. However, the infodemic wave around vaccines, it is information which mixed into one between hoax and accurate vaccine information circulating in large quantities on social media, has caused the Covid-19 vaccination program to face obstacles. Based on the facts found, some people from the generation Z group have not decided to vaccinate. The reason is because they are not sure about the effectiveness of the vaccine and there is still a lot of unclear vaccine information circulating on social media. This has an impact on the way Generation Z elaborates the Covid-19 vaccine information message. Message elaboration is the process of receiving and evaluating information carefully and critically. Therefore, this study aims to determine how much the elaboration of the Covid-19 vaccine infodemic message can influence generation Z's vaccination decision making. This study uses the elaboration likelihood model theory to determine the information reception route used by generation Z when elaborating the Covid-19 vaccine infodemic message. The method used in this research is explanatory quantitative with a positivistic paradigm and purposive sampling data collection techniques. The results obtained in this study stated that the elaboration of the Covid-19 vaccine infodemic message had a significant influence on generation Z vaccination decision making with a value of 54.4%. Generation Z's vaccination decision making is determined by the high intensity of elaboration of the Covid-19 vaccine infodemic message on social media